PENERAPAN MODEL PEMBELAJARAN PEER LED GUIDED INQUIRY (PLGI) PADA POKOK BAHASAN STRUKTUR ATOM DI KELAS X MIA MAN 2 MODELPEKANBARU - Nora Yulita; Jimmi Copriady; Abdullah Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purposes of research are to know the improvement of student learning achievement and value of influence by implementing Peer Led Guided Inquiry (PLGI) learning model on the atomic structure subject in the class X MIA MAN 2 Model Pekanbaru. The from of the study was an experiment with a randomizedControl Group Pretest-Posttest. The sample in the X MIA 4class experimental class and the X MIA 3 a the control class randomly determined after the normality test and homogeneity test. The experimental class was treated with the application of learning Peer Led Guided Inquiry (PLGI) namely, data analisysis for hypothesis testing is done using the right-party t-test. Based on the results of data analysis obtained thitung = 9,5thitungand ttable = 1,67. And obtained that t count>ttable= 9,5> andttable = 1,67means the applicationof PLGI learning model can improve student learning outcomes on the subject of atomic struktur.Key Words : Learning Model Peer Led Guided Inquiry (PLGI), Learning Achievement, Atomic Structure